The Effect of Health Education on Low-Salt Diet Knowledge in Hypertensive Patients at Limboto Health Center - Dhea Putri Puluhulawa; Nasrun Pakaya; Sitti Fatimah M. Arsad (Universitas Muhammadiyah Palu, 2026)
Hypertension is one of the non-communicable diseases with an increasing prevalence and is a public health problem because it is often asymptomatic but at risk of causing serious complications. One of the non-pharmacological efforts that plays an important role in controlling hypertension is the implementation of a low-salt diet. However, low patient knowledge about low-salt diets is still a major obstacle in the management of hypertension. This study aims to determine the effect of health education on the knowledge of low-salt diets in hypertensive patients at the Limboto Health Center. This study uses a quantitative design with a pre-experimental approach through one group pretest-posttest design. The study population is hypertension patients recorded in November 2025 with a sample of 44 respondents taken using purposive sampling techniques. Data collection was carried out using a low-salt diet knowledge questionnaire that has been tested for validity and reliability. Health education is provided through counseling methods using leaflet and Power Point media. Data analysis was carried out using the Paired Sample T-Test to see differences in knowledge levels before and after health education. The results of the study showed that after being given health education, most hypertensive patients had a good level of low-salt diet knowledge but still found patients with sufficient and insufficient knowledge levels. These findings show that there is a knowledge gap in some patients regarding the implementation of a low-salt diet. This study emphasizes the importance of continuous health education by health workers to improve patient understanding in hypertension control.